Effects of Graded Doses of Vitamin E on Blood and Serum Biochemistry of Sheep - Faiza Hakeem,; Muhammad Zubair,; Muhammad Shahbaz,; Sayyad Murtaza Hassan Andrabi,; Zulfiqar Hussain Kuthu,; Sohail Ahmed,; Fatima, Mehreen; Zulfiqar Ahmed,; Nasir Hameed, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Vitamin E (Vit. E) is primarily responsible for the increased antioxidant capacity observed in animal studies. The present research aimed to investigate vitamin E’s effect on haematological and serum biochemical parameters in Kail sheep. Eighteen (18) Kail breed ewes older than two years but not yet pregnant were chosen for this experiment. The animals were randomly divided into three groups (Control, T1, and T2). During the entire experiment, the control group had access to pure water. Vitamin E was administered orally to both groups of ewes daily for 30 days, with Group T1 receiving 150 mg/kg body weight and Group T2 receiving 200 mg/kg body weight. Blood samples were collected on days 0, 15, and 30. The results revealed a significant increase in blood biochemistry parameters such as RBC, HGB, RDW %, WBC, LYM concentration, and LYM (%) in sheep fed Vitamin E. The serum concentration of albumin, globulin, total protein, and AST was significantly increased (P< 0.05). We conclude that the haematological and serum biochemical parameters in Kail sheep were enhanced after an oral dose of vitamin E.